2006
DOI: 10.1088/0253-6102/46/2/020
|View full text |Cite
|
Sign up to set email alerts
|

Pomeron-Quark Coupling from Charge Conjugation Invariance

Abstract: Based on the charge conjugation invariance and the vacuum property of the Pomeron, we point out that the commonly used vector vertex of the Pomeron coupling to quark is incorrect since it contradicts with the Pomeron property. We also claim that the soft Pomeron could be a tensor glueball ξ(2230) with quantum numbers IGJPC = 0+2++ and total decay width Γtot≃100 MeV, which lies on the soft Pomeron trajectory αp = 1.08+0.20t. Therefore, the coupling vertex of the soft Pomeron to quark should be tensorial which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
(10 reference statements)
0
6
0
Order By: Relevance
“…We observed that the amplitude F + (s, t) is the same for particle-particle and particle-antiparticle scattering and thus corresponds to an exchange of even (or positive) C-parity, C=+1, The amplitude F − (s, t) changes sign when going from the particle-particle to the particleantiparticle scattering process and can hence be understood to have odd (or negative) C-parity, C = −1. The amplitude F + (s, t) hence has vacuum quantum numbers and it is dominated at high energy by the Pomeron exchange which identifies as Tensor Glueball ξ(2230) with quantum numbers I G J P C = 0 + 2 ++ , mass of 2.23 GeV, and decay width Γ ξ = 100 MeV [10] . The dominant contribution to the amplitude F − (s, t) comes from the Odderon which is made up of three Reggeized gluons and is a colorless bound state of the three gluons.…”
Section: Even and Odd Scattering Amplitudes Under-crossing Symmetrymentioning
confidence: 99%
“…We observed that the amplitude F + (s, t) is the same for particle-particle and particle-antiparticle scattering and thus corresponds to an exchange of even (or positive) C-parity, C=+1, The amplitude F − (s, t) changes sign when going from the particle-particle to the particleantiparticle scattering process and can hence be understood to have odd (or negative) C-parity, C = −1. The amplitude F + (s, t) hence has vacuum quantum numbers and it is dominated at high energy by the Pomeron exchange which identifies as Tensor Glueball ξ(2230) with quantum numbers I G J P C = 0 + 2 ++ , mass of 2.23 GeV, and decay width Γ ξ = 100 MeV [10] . The dominant contribution to the amplitude F − (s, t) comes from the Odderon which is made up of three Reggeized gluons and is a colorless bound state of the three gluons.…”
Section: Even and Odd Scattering Amplitudes Under-crossing Symmetrymentioning
confidence: 99%
“…The summary and concluding remarks are given in Sec. 4, where from the study of the interference between F + (s, t) and F − (s, t) amplitudes we conclude which are the best experiments to be done in order to detect in a clear way the Odderon.…”
Section: Introductionmentioning
confidence: 94%
“…Since the Pomeron is described by a colorless bound state of interacting Reggeized gluons in the t-channel one can expects that the physical states on the Pomeron trajectory should be glueball states with the largest spin. The lowest of these states is J P C 2 ++ glueball consisting of two constituent gluons with mass of 2.23 GeV, [4] ξ(2230). The fact that the internal gauge symmetry group of QCD has rank greater than one permits to construct from three gluons a charge conjugation (C)-odd state.…”
Section: Introductionmentioning
confidence: 99%
“…The amplitude F + (s, t) hence has vacuum quantum numbers and it is dominated at high energy by the Pomeron exchange, which identifies as tensor glueball ξ(2230) with quantum numbers I G J P C = 0 + 2 ++ , mass of 2.23 GeV, and decay width Γ ξ = 100 MeV. [11] The dominant contribution to the amplitude F − (s, t) comes from the Odderon, which is made up of three Reggeized gluons and is a colorless bound state of the three gluons. Therefore, studying the contribution from amplitude F − (s, t) is equivalently to study the Odderon contribution to hadron-hadron scattering cross section at high energies.…”
Section: Theory and Formalismmentioning
confidence: 99%